Medicina y redes sociales: ¿Qué hacer ante la desinformación médica? - Rodríguez León, Arnaldo; Hernández de la Rosa, Yurima; Moreno-Martínez, Francisco L. (CorSalud, 2019)
Medicina y redes sociales: ¿Qué hacer ante la desinformación médica?